Transverse myelitis following COVID-19 infection. What is the mechanism? A case report and literature review - Babak Alijani; Alia Saberi; Parham Niyasti; Mohammad Haghani Dogahe (Romanian Journal of Neurology, 2021)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreak became one of the most global health challenges in the recent century. Transverse myelitis is a rare medical condition reported in few case reports following COVID-19 infection. We present a 63 years old female with post-COVID-19 transverse myelitis. The patient had paraplegia combined with autonomic symptoms and T4 sensory level. Initial treatment started with methylprednisolone. Since the patient did not respond to the prednisolone, plasmapheresis was considered for the patient. Unfortunately, the patient could not tolerate the plasmapheresis. We considered rituximab for the next plan, but unfortunately, the patient died due to respiratory failure. To date, there is no published study to evaluate different mechanisms of post/para COVID-19 transverse myelitis. However, the post/para COVID-19 transverse myelitis mechanism seems to be heterogeneous; the activation of a silent autoimmune disease can probably justify some unusual clinical presentations of a viral illness. Further studies are needed to categorize the underlying mechanisms of post/para COVID-19 transverse myelitis and effective treatments regarding the primary pathology.